1989
DOI: 10.2307/3577405
|View full text |Cite
|
Sign up to set email alerts
|

A Model Relating Cell Survival to DNA Fragment Loss and Unrepaired Double-Strand Breaks

Abstract: The model of radiation action that is presented relates the surviving fraction of irradiated cells to unrepaired DNA double-strand breaks (DSBs). The following assumptions are made in the model: (i) A DNA fragment created by the induced DSBs may move out of its chromosome (become lost), and the probability of that process depends on the fragment size. (ii) An irradiated cell will lose its proliferative capacity if it has an unrepaired DSB (including DNA fragments) at certain points in the cell cycle. Mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
15
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 44 publications
4
15
0
Order By: Relevance
“…Then RSV is not protector against cell killing in vitro or lethality in vivo (54). However, results of other studies may indicate that it would protect against lethality, but the doses of irradiation used were much lower (55,56). Above results were confirmed by our, where the mortality of mice from groups of 1 Gy + RSV were higher compared to 1 Gy alone, and clear mitigation of DNA damage was seen after combined exposure to 0.5 Gy daily and RSV.…”
Section: Discussionsupporting
confidence: 81%
“…Then RSV is not protector against cell killing in vitro or lethality in vivo (54). However, results of other studies may indicate that it would protect against lethality, but the doses of irradiation used were much lower (55,56). Above results were confirmed by our, where the mortality of mice from groups of 1 Gy + RSV were higher compared to 1 Gy alone, and clear mitigation of DNA damage was seen after combined exposure to 0.5 Gy daily and RSV.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, the residual unrepaired dsb represent dsb remaining in a DNA molecule until the moment when the time available for dsb repair (t fep) is over . It was shown that the residual unrepaired dsb become new DNA fragments or 'misrepair' chromosomal aberrations (CA) after t rep has elapsed .Several quantitive estimates from the model, which agree with experimental data, support the validity of this model (Ostashevsky 1989) : (1) the number of PCC fragments and the total number of CA for AT, normal fibroblasts (NF) and LY-R cells ;(2) an increase in the number of 'misrepair' CA for NF cells treated with araA ;(3) tfep values for AT, NF and Ehrlich ascites tumour (EAT) cells (see § 2 .2 .3 for EAT cells) ; (4) the difference between t ree values for delayed and immediately plated NF and V-79 cells . More details of the model are given in § 2 .…”
supporting
confidence: 53%
“…
A model developed previously (Ostashevsky 1989), was applied to calculate survival curves from the DNA double-strand break (dsb) repair data for Ehrlich ascites tumour (EAT) cells irradiated with X-rays or 3 . 4 MeV a-particles (Blucher 1988) .
…”
mentioning
confidence: 99%
“…30% ALSs, 63-67% SSBs, and 4-7% DSBs) are the lesions most responsible for opening the condensed chromatin structure after irradiation, seen as EHD. The decondensation of chromatin may be prerequisite for the loss of DNA fragments (between two DSBs), an event postulated to occur very early post irradiation in the DSB model (Ostashevsky 1989(Ostashevsky , 1990. Thus, although the repair rates measured here for EHD are consistent with SSB repair, they could be very important for determining the fraction of DSBs repaired and survival.…”
Section: Discussionmentioning
confidence: 75%